2021
DOI: 10.1063/5.0059908
|View full text |Cite
|
Sign up to set email alerts
|

How coronavirus survives for hours in aerosols

Abstract: COVID (CoronaVirus Disease)-19, caused by severe acute respiratory syndrome-CoronaVirus-2 (SARS-CoV-2) virus, predominantly transmits via airborne route, as highlighted by recent studies. Furthermore, recently published titer measurements of SARS-CoV-2 in aerosols have disclosed that the coronavirus can survive for hours. A consolidated knowledge on the physical mechanism and governing rules behind the significantly long survival of coronavirus in aerosols is lacking, which is the subject of the present invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
15
0
1
Order By: Relevance
“…We have observed that the droplets of size 25 µm evaporates to aerosols with mean radius of 2 µm. The motion of these aerosols are controlled by the diffusive force and therefore, these droplets have the ability float in the air for longer time (see also [35]). The results displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have observed that the droplets of size 25 µm evaporates to aerosols with mean radius of 2 µm. The motion of these aerosols are controlled by the diffusive force and therefore, these droplets have the ability float in the air for longer time (see also [35]). The results displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…En el caso del SARS-CoV-2, estudios demuestran que puede mantenerse activo en aerosoles y superficies, no obstante, es inactivado por desinfectantes comunes como alcohol o peróxido de hidrógeno, en tal sentido, un protocolo adecuado de limpieza y desinfección de mobiliario y equipamiento constituye una de las principales herramientas para prevenir el contagio por coronavirus en los recintos universitarios. Adicionalmente es importante complementar esta medida con la verificación y análisis periódico de las superficies, mediante ensayos para la detección del SARS-CoV-2, que valide los procedimientos de limpieza y desinfección y garantice un espacio académico más seguro para las clases presenciales y semipresenciales (Lema, 2020;Chatterjee et al, 2021).…”
Section: Discussionunclassified
“…It has been researched with the aim of providing a solution to the famous SARS-CoV-2, but all these studies are based on explaining the functioning of the exhaled air to the environment, which is the route of contagion of all diseases, either by major droplets or by aerosols, according to Leung et al 4 . The human body exhales particles between 10 µm and 100 µm of diameter in a sneeze, according to the numerical study of Chillón et al 4 , but it is not considered aerosol until the particle reaches 5 µm of diameter, Chatterjee et al 5 . When a person coughs, speaks, or sneezes, exhales to the environment particles with great contagion power.…”
Section: Introductionmentioning
confidence: 99%